2016
DOI: 10.1038/srep29619
|View full text |Cite
|
Sign up to set email alerts
|

Non-responsiveness to intravitreal aflibercept treatment in neovascular age-related macular degeneration: implications of serous pigment epithelial detachment

Abstract: The prognosis of neovascular age-related macular degeneration (AMD) has been improved by anti-vascular endothelial growth factor treatments, including intravitreal aflibercept (IVA) treatment. However, many patients remain incurable. In this study, we retrospectively evaluated non-responsiveness to IVA monotherapy at 12 months in 133 eyes of 133 AMD patients. Sixty-two patients were initially treatment-naive, and 71 had received other treatments before IVA (the treatment-switched group). Mean best-corrected vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
3
39
1
2
Order By: Relevance
“…However, complete regression of CNV cannot be achieved with anti-VEGF monotherapy. Therefore, some cases are refractory to anti-VEGF monotherapy, while some cases exhibit high recurrence [6]. …”
Section: Introductionmentioning
confidence: 99%
“…However, complete regression of CNV cannot be achieved with anti-VEGF monotherapy. Therefore, some cases are refractory to anti-VEGF monotherapy, while some cases exhibit high recurrence [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarded the presence of IRF as a negative prognostic biomarker for the functional outcome [24,25] . Interestingly, we observed a decrease of intraretinal edema on average by 80% within the first 7 days after an intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been showed that the incidence for non responsiveness to bevacizumab in treatment naïve n-AMD ranges between approximately 40 and 50% while as the percent of non responsiveness to ranibizumab was between approximately 10-20% [6][7][8][9]. Although there is currently no more evidence in the literature, a recent report demonstrated that the rates of non responsiveness to aflibercept in the treatment of n AMD based on best corrected visual acuity (BVCA) and fundus findings were approximately 8% and 13%, respectively [10].…”
Section: Editorialmentioning
confidence: 98%
“…In the light of the recent reports, it can be considered that the potential risk factors for non-responsiveness to anti-VEGF agent in the treatment of n-AMD are an initial lesion with subfoveal fibrosis or atrophy in retina pigment epithelium and photoreceptors, lesion in large size, type 1 choroidal neovascularization, serous pigment epithelium detachment (PED), haemorrhagic PED, fibrovascular PED, polypoidal choroidal vasculopathy, foveal scarring and vitreomacular traction, outer retinal tubulation, cystoid degeneration in outer retina, genetic disposition or an anti-VEGF resistance [Table 1, 13-22]. Table 1: The possible risk factors for non-responsiveness to anti-VEGF agents in the patients with nAMD [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation